A clear sky irradiation assessment using a modified Algerian solar atlas model in Adrar city. (November 2018) - Marif, Y.; Chiba, Y.; Belhadj, M.M.; Zerrouki, M.; Benhammou, M.
Abstract: The solar systems technology offers a promising method for the large scale use of solar energy in the southern zone of Algeria. The magnitude of solar radiation is the most important parameter for sizing these systems. The chief goal of this investigation is to contribute to the national efforts in establishing solar radiation in Algeria. Using the Algerian solar atlas model and the experimental monthly mean Linke turbidity factor a new model for the prediction of the solar radiation in the Sahara desert area of Adrar region, Algeria is developed. In this study, the Linke turbidity factor was obtained from radiometric and meteorological data recorded in the research unit in renewable energies in the Saharan medium, during October 2012 to May 2015. This investigation finds that the newly developed model performs more accurate estimation, with smaller relative errors between measured and computed values.